THE IMPACT OF SOCIAL MEDIA ON YOUTH COGNITIVE DEVELOPMENT - Shoimova Farangiz, (TADQIQOTLAR, 2026)
Abstract: In today’s digital era, social media has become an inseparable part of the daily lives of young people all over the world. Rapid technological advancements and  the  increasing  accessibility  of  the  internet  have  transformed  the  way  youth communicate, learn, and develop cognitively. Millions of young users access social media platforms every minute, seeking information, exchanging ideas, building social connections,  and  shaping  their  perceptions  about  life.  With  this  transformation, significant questions arise: How does the constant exposure to an endless stream of information influence young minds? To what extent does social media  usage affect attention span, memory, and critical thinking? This article aims to provide an in-depth analysis  on  how  social  media  is  influencing  the  cognitive  development  of  young individuals, focusing on both the positive opportunities that are opening up and the concerning challenges that are emerging.